Born migrators: Historical biogeography of the cosmopolitan family Cannabaceae. Issue 4 (12th December 2019) - Jin, Jian‐Jun; Yang, Mei‐Qing; Fritsch, Peter W.; van Velzen, Robin; Li, De‐Zhu; Yi, Ting‐Shuang
Abstract: Dispersal scenarios have been favored over tectonic vicariance as an explanation for disjunct distributions in many plant taxa during the last two decades. However, this argument has been insufficiently addressed in cosmopolitan groups showing disjunct patterns in both the temperate and tropical regions. In this study, we used the Cannabaceae, an angiosperm family distributed in tropical and temperate regions of both the New World and the Old World, to explore the role of dispersal in shaping disjunct patterns and species diversification of cosmopolitan plants. We reconstructed the phylogenetic relationships of all 10 genera and 75 species of Cannabaceae (ca. 64.1% of recognized species) based on eight DNA regions. Based on fossil calibrations, we estimated the divergence times and net diversification rates. We further inferred the ancestral geographical ranges with several models and compared the fitness of different models. The Cannabaceae and most genera were strongly supported as monophyletic except for the Parasponia being embedded within the Trema . The Celtis were resolved into two strongly supported clades primarily corresponding to temperate and tropical regions. We inferred that the Cannabaceae originated at ca. 93 Ma, and that subsequent rampant and widespread dispersals shaped the intercontinentally disjunct distribution of the Cannabaceae. Dispersal coincides with adaptation to drier and colder climate in the Northern Hemisphere, or humid and warm climate in the tropical regions, followed by rapid species diversification. This study advances our understanding as to the formation of distribution patterns and species diversification of a plant family with tropical to temperate disjunct distributions.